2020
DOI: 10.1097/mao.0000000000002951
|View full text |Cite
|
Sign up to set email alerts
|

Precise Evaluation of the Cochlear Duct Length by Flat-panel Volume Computed Tomography (fpVCT)—Implication of Secondary Reconstructions

Abstract: Hypothesis: Flat-panel volume computed tomography (fpVCT) and secondary reconstruction allow for more accurate measurements of two-turn length (2TL), cochlear duct length (CDL), and angular length (AL). Background: Cochlear geometry is a controversially debated topic. In the meantime, there are many different studies partly reporting highly divergent values. Our aim is to discuss the differences and to propose a radiological possibility to improve cochl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 50 publications
1
18
0
2
Order By: Relevance
“…Indeed, the use of fpVCT SECO in this study, revealed the above mentioned advantages, in addition to the obvious reduced metal artifacts [20,21]. The demonstrated results are in accordance with recently published data on measurements of CDL OC using fpVCT SECO in temporal bone specimen [24] using multi-planar reconstructions [38]. This might be well explained by the higher resolution of fpVCT SECO with a slice thickness of 99 µm in comparison to the other image qualities.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Indeed, the use of fpVCT SECO in this study, revealed the above mentioned advantages, in addition to the obvious reduced metal artifacts [20,21]. The demonstrated results are in accordance with recently published data on measurements of CDL OC using fpVCT SECO in temporal bone specimen [24] using multi-planar reconstructions [38]. This might be well explained by the higher resolution of fpVCT SECO with a slice thickness of 99 µm in comparison to the other image qualities.…”
Section: Discussionsupporting
confidence: 91%
“…Due to the larger artifacts of the electrodes in MSCT, the points marking the lateral wall might be set more laterally than in the true anatomical set, responsible for the discrepancies in different parameters. Therefore, clinical analyses using fpVCT SECO probably represents the true length, since assessments with micro-fpVCT and micro-CT in temporal bone specimens have shown no significant different CDL at the lateral wall values up to over 40 mm [13,24], which corresponds to a CDL OC of about 35 mm. In line with this, in other studies, shorter CDL values have been reported in clinical modalities [8,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the sample size might be too small, but previous studies investigating the CDL have shown that a number of 10 is adequate to obtain sufficient statistical power. 7 , 41 , 42 …”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, multislice computed tomography (CT) 3 , 4 and cone beam CT 5 , 6 are most commonly used. Experimental imaging systems such as micro-CT 5 , 7 and synchrotron imaging 8 have been shown to be more precise, but they are not applicable for use in humans due to their higher radiation exposure and the need for small imaging volumes.…”
mentioning
confidence: 99%